2015
DOI: 10.1016/j.ophtha.2014.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Ranibizumab for Diabetic Macular Edema with Prompt versus Deferred Laser Treatment: 5-Year Randomized Trial Results

Abstract: Objective To report 5-year results from a previously reported trial evaluating intravitreal 0.5-mg ranibizumab with prompt versus deferred (for ≥24 weeks) focal/grid laser treatment for diabetic macular edema (DME). Design Multicenter randomized clinical trial. Participants Among participants from the trial with 3 years of follow-up who subsequently consented to a 2-year extension and survived through 5 years, 124 (97%) and 111 (92%) completed the 5-year visit, in the prompt and deferred groups, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
330
2
15

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 465 publications
(374 citation statements)
references
References 6 publications
(8 reference statements)
13
330
2
15
Order By: Relevance
“…After three-year follow-up, the mean visual change was +9.7 letters in the ranibizumab with deferral laser, significantly better than +6.8 letters in the ranibizumab with prompt laser [3]. Although the five-year visual outcome revealed similar visual gains (+7.2 and +9.8 letters) were observed between the ranibizumab with prompt and deferral laser, better visual outcome was detected in the deferral laser (+17 letters) than in the prompt laser (+10 letters) in the subgroup with poor baseline vision [4]. Fewer cumulative ranibizumab injections were required in the ranibizumab with prompt laser group (median 13 injections) than in the ranibizumab with deferral laser group (median 17 injections).…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…After three-year follow-up, the mean visual change was +9.7 letters in the ranibizumab with deferral laser, significantly better than +6.8 letters in the ranibizumab with prompt laser [3]. Although the five-year visual outcome revealed similar visual gains (+7.2 and +9.8 letters) were observed between the ranibizumab with prompt and deferral laser, better visual outcome was detected in the deferral laser (+17 letters) than in the prompt laser (+10 letters) in the subgroup with poor baseline vision [4]. Fewer cumulative ranibizumab injections were required in the ranibizumab with prompt laser group (median 13 injections) than in the ranibizumab with deferral laser group (median 17 injections).…”
Section: Editorialmentioning
confidence: 99%
“…The pathophysiology of macular edema involves both the presence of inflammation and angiogenic stimulant regarding vascular endothelial growth factor (VEGF) [1]. Intravitreal injections of anti-VEGF, including ranibizumab [2][3][4][5][6][7][8], bevacizuamb [9], pegaptanib [10], aflibercept [11] are proven to be effective for managing DME. Intravitreal injections of corticosteroids, potent anti-inflammatory agents, such as fluocinolone acetonide implants (Retisert) [12], fluocinolone acetonide inserts (Iluvein) [13,14], dexamethasone implants [15,16], and triamcinolone acetonide [2] have been shown to be beneficial to DME.…”
mentioning
confidence: 99%
“…Aflibercept in diabetic macular edema: evaluating efficacy as a primary and secondary therapeutic option Anti-vascular endothelial factors (anti-VEGFs) have become the standard of care in the treatment of diabetic macular edema (DME) after several randomized clinical trials (RCTs) established their efficacy compared with other treatment modalities such as laser therapy and steroids. [1][2][3] There are currently three anti-VEGF drugs that are available for clinical practice; aflibercept (Eylea, Regeneron Pharmaceuticals, Tarrytown, NY, USA), bevacizumab (Avastin, Genentech, South San Francisco, CA, USA), and ranibizumab (Lucentis, Genetech, South San Francisco, CA, USA). Aflibercerpt, previously known as VEGF Trap-EYE, is a 115-kDA recombinant fusion protein consisting of the VEGF binding domains of human VEGF receptors 1 and 2 fused to the Fc Domain of human immunoglobulin-G1.…”
mentioning
confidence: 99%
“…5 Both ranibizumab (Lucentis) and bevacizumab (Avastin) have been studied extensively in several large randomized controlled trials in the treatment of DME. 1,2,6,7 Patients treated with both drugs have shown excellent visual gains, long term stability and improved anatomy compared with grid laser treatment and steroid injections, making them the first line treatment for visual loss associated with DME. 2 A study by Regnier et al 8 showed that the lifetime cost of treating patients with DME in the UK was £20 019 for ranibizumab PRN and £25 859 for aflibercept using a bimonthly dosing regimen.…”
mentioning
confidence: 99%
See 1 more Smart Citation